(untitled) (Africa Development, 2022)
Contents ARTICLES P. Anyang Nyong'o Liberals Models of Capitalist Development in Africa : Ivory Coast ....................... 5 Résumé ......................... 20 S. Bedrani La Technologie Agricole en Algérie ......................... 21 Summary ......................... 39 A. Chilivumbo On rural development : a note on Malawi's Programmes of Development for exploitation ................... 41 Résumé .......................... 54 H. Galboume Some aspects of ideological functions in the Development of the Post-Colonial State in Tanzania ................ 57 Résumé ......................... 73 BOOK REVIEWS Β. Founou-Tchigoua Makhtar Diouf - Echange 'inégal et ordre économique international ......................... 75 J. R. Herzoc Towards a theory of Rural Development .......................... 79 FOCUS ON RESEARCH AND TRAINING INSTITUTES DEVELOPMENT STUDIES AND RESARCH CENTRE, UNIVERSITY OF KHARTOUM ......................... 89 CENTRE DE RECHERCHES INTERDISCIPLINAIRE POUR LE DEVELOPPEMENT DE L'EDUCATION, UNIVERSITE NATIONALE DU ZAIRE, KISANGANI ...................... 93